PERENCANAAN OPERASIONAL INDUSTRI MINYAK KAYU PUTIH DENGAN MEMANFAATKAN IOT PADA PT. FDF - Eko, Ferdianyah; Syah, Tantri Yanuar Rahmat; Hamdi, Edi; Sunaryanto, Ketut (Politeknik Negeri Ambon, 2025)
Introduction: This aims to assess how IoT can increase efficiency in the eucalyptus oil production process.Method: This activity employs surveys, interviews, and case studies to identify problems in planning the development of the eucalyptus oil industry, and to design and implement technology-based solutions that improve quality and efficiency.Result: PT FEAR DENSU FARM uses the SCFE method combined with IoT Technology to extract eucalyptus leaves. The SCFE method is safer for the environment and reduces the risk of hazardous chemical contamination. Unlike conventional extraction methods using solvents that must be removed separately after extraction, SCFE leaves no chemical residue in the final product. Keywords: Internet of Things, Eucalyptus Oil, Operational Planning, Business Plan